MASTER’S DEGREE IN LAW - PER ASPERA AD ASTRA BALTIC APPROACH - Šulmane, Dace; Beinoravičius, Darijus; Kaugia, Silvia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The purpose of this article is to continue the discussion of experts and academic representatives on the necessary knowledge and examination formats in law studies in order to achieve the goal: providing the education of highly qualified lawyers to fully and responsibly implement the rule of law in democratic countries. Authors highlight the current trends and novelties in the Baltic States, which illustrate the transformation of the attitude of legislators and policymakers and the steps taken to ensure the highest standards in learning the legal profession. The article illustrates the differences in the procedure for obtaining a master's degree in Latvia, Lithuania and Estonia, which is related to the introduction of the national unified legal professional qualification exam in Latvia in 2021. The article summarizes the opinions of three academic staff and legal professionals from the Baltic States on how the master's degree acquisition process existing in the country provides guarantees for graduates' acquisition of quality education and the necessary professional skills.